First enantiospecific synthesis of (-)-parvifoline and (-)-curcuquinone - Chavan, Subhash P.; Thakkar, Mahesh; Jogdand, Ganesh F.; Kalkote, Uttam R. (Journal of Organic Chemistry, 2006)
The first enantiospecific synthesis of (-)-parvifoline, employing ring-closing metathesis as the key step, and (-)-curcuquinone from naturally occurring (R)-(+)-citronellal is described.